Analytical Artefacts Preclude Reliable Isotope Ratio Measurement of Internal Water in Coral Skeletons. Issue 3 (12th July 2022) - de Graaf, Stefan; Vonhof, Hubert B.; Reijmer, John J. G.; Feenstra, Eline; Mienis, Furu; Prud'Homme, Charlotte; Zinke, Jens; van der Lubbe, Jeroen H. J. L.; Swart, Peter K.; Haug, Gerald
Abstract : Internal water in cold‐water and tropical coral skeletons was extracted and measured for its oxygen and hydrogen isotope ratios. Water was extracted by crushing pieces of coral hard tissue in a percussion device connected to either a cavity ring‐down spectroscopy (CRDS) system or an isotope ratio mass spectrometry (IRMS) system. Despite most samples yielding sufficient water, each analytical system produces distinct isotope patterns. Experiments show that several characteristics specific to biominerals give rise to discrepancies and analytical artefacts that preclude the acquisition of reproducible isotope data. The main complication is that internal water in biogenic carbonates is distributed in an open interconnected micro‐network that readily exchanges with external water and potentially facilitates interaction with hydration water in the finely dispersed organic matrix in the coral skeleton. Furthermore, only an isotopically fractionated part of the internal water is released from the coral skeletons upon crushing. Altogether, isotope ratio measurement of internal water in corals with bulk crushing techniques does not give primary fluid isotope ratios useful for (palaeo‐)environmental or microbiological studies. As the resulting isotope patterns can show systematic behaviour per technique, isotope data may be erroneously interpreted to reflect the original calcifying fluid when using only a single technique to isotopically characterise internal fluids in coral skeletons. Abstract : Key Points Free water trapped inside coral skeletons was extracted and isotopically analyzed on two commonly used techniques for fluid inclusion isotope analysis. Measured oxygen and hydrogen isotope ratios do not reproduce between the techniques due to several analytical artefacts. The water extracted from coral skeletons is not of primary origin.